PEMODELAN SISTEM LEVEL AIR HEAD TANK MENGGUNAKAN PENGENDALI PID PADA PEMBANGKIT LISTRIK TENAGA MINI HIDRO MERASAP - ., Ihdina Nurkarima (Faculty of Engineering, Universitas Tanjungpura, 2014)
Mini-hydro power plant is a micro power plant that utilizes the river flow as its energy generator. Size of the power generated from the plant is affected by the capacity of the water in the head tank. Head tank served as a container of water in the reservoir end of the plant which supplies water to spin turbines rapidly through the penstock. Less precised control of water level in the head tank can result in less optimum work of the system to fulfill electric power capacity required at the plant. The purpose of this research is to design an automatic water level control system in order to fulfill the load on the generator using PID controller. In this design, the method used for PID controller tuning parameters is the quarter amplitude decay method and compared with Ziegler-Nichols oscillation method. This method was chosen because it could produce a better system than the method of trial and error. Simulations were performed by using Matlab 7.6 software to get graphs of stability and transition response, and steady state response at the system. The results showed that the system could reach the setpoint, that was 6 meter high, with the controller parameter values Kp= 1390. System specifications consist of obtained based on that controller parameters, with system response in form of step function, consist of maximum overshoot Mp= 35,1%, rising time tr = 0.178 seconds and setltling time ts= 1.49 seconds. Based on the values acquired, it was concluded that the system had a better performance with PID controller. Keywords : mini-hydro power plant, head tank, water level, PID controller, quarter amplitude decay method, Ziegler-Nichols method